Improving Student Activities and Learning Outcomes at MI NW Repok Are through the Utilization of Learning Slides - Herlina (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve the attention of students in Class IV MI NW Repok Are by utilizing learning slides. This Classroom Action Research (CAR) uses the Kemmis and Taggart research model. The research flow consists of (1) Planning, (2) Action, (3) Observation (4) Reflection. The subjects of this study were 20 students in Class IV MI NW Repok Are. The research data were obtained using student attention observation sheets. Verbal data from observations were analyzed using qualitative descriptive techniques with simple formulas. The results of the study showed that the use of learning slides can improve the attention of students in Class IV MI NW Repok Are. The attention of students from each indicator of activity increased. In cycle I, the indicators entered the moderate category as many as 2 indicators out of 5 existing indicators, in cycle II there was an increase, namely the moderate category indicators decreased to 1 indicator. Based on the research above, it can be concluded that the use of learning slides can improve students' attention.